2023
DOI: 10.15294/jpii.v12i1.39713
|View full text |Cite
|
Sign up to set email alerts
|

Project-Based Learning and Problem-Based Learning Models in Critical and Creative Students

Abstract: This research is experimental research with a 2 x 2 factorial design involving students in the critical and creative categories. Data collection used a description test instrument. Data were analyzed inferentially by hypothesis testing ANACOVA comparison. Problem-Based Learning (PBL) directs students to learn, directs individual and group investigations, generates and performs work, and assesses the problem-solving process. While the syntaxes for Project-Based Learning (PjBL) are starting learning with essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…These findings are consistent with previous studies that found no differences in learning outcomes between SBL and PjBL classes (Aghayani & Hajmohammadi, 2019;Frengley et al, 2011;Kızkapan & Bektaş, 2017;B.-O. Lee et al, 2019;Pan et al, 2023;Rahmati et al, 2022;Smelt et al, 2015;Suradika et al, 2023), Self-regulation (Erdogan & Senemoglu, 2017) was found to have a significant effect on academic performance in the logistic regression analysis. The analysis includes four models, PM1 to PM4, which categorize GPA.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with previous studies that found no differences in learning outcomes between SBL and PjBL classes (Aghayani & Hajmohammadi, 2019;Frengley et al, 2011;Kızkapan & Bektaş, 2017;B.-O. Lee et al, 2019;Pan et al, 2023;Rahmati et al, 2022;Smelt et al, 2015;Suradika et al, 2023), Self-regulation (Erdogan & Senemoglu, 2017) was found to have a significant effect on academic performance in the logistic regression analysis. The analysis includes four models, PM1 to PM4, which categorize GPA.…”
Section: Discussionsupporting
confidence: 92%
“…(Gunawan et al, 2017). This is in line with research conducted by Susanti and friends (Susanti et al, 2022) shows that there is an increase in student learning motivation through the use In addition, it can also improve students' creative thinking skills and increase learning effectiveness to obtain high learning outcomes (Suradika et al, 2023;Yanti et al, 2023;Yufrizal, 2021). Other research conducted by Chan Lin (ChanLin, 2008) regarding the use of technology in project-based learning also showed that all students who participated in the project were able to achieve their project objectives as evidenced by their achievements related to the development of skills and abilities to synthesise and elaborate knowledge, their positive attitudes to participating in scientific exploration, and their willingness to use technology to conduct and report their research.…”
Section: Resultssupporting
confidence: 86%
“…Based on the results of the study, the scores of students were obtained which were then converted into student scores and then analyzed by calculating N-Gain. The N-Gain value is the difference between the post-test and pretest scores to determine the increase in value that occurs (Aprida & Mayarni, 2023;Dewi et al, 2023;Wahyuddin et al, 2023). To obtain data on the results of the study, learning was carried out project-based learning model.…”
Section: Methodsmentioning
confidence: 99%
“…Sample determination was carried out by total sampling to determine research subjects. The learning model applied is project-based learning with the syntax as in Table 1 (adapted by Suradika et al, 2023). The collaborative skills assessment instrument was developed from Greenstein (2012) with measurement variables including working productively, showing respect, compromise, and responsibility.…”
Section: Methodsmentioning
confidence: 99%